Treatment of benign prostatic hyperplasia and abnormal ejaculation: live imaging reveals tamsulosin – but not tadalafil – induced dysfunction of prostate, seminal vesicles and epididymis. Issue 6 (7th November 2022) - Seidensticker, Mathias; Tasch, Sabine; Mietens, Andrea; Exintaris, Betty; Middendorff, Ralf
Abstract : In brief: One of the most commonly prescribed benign prostatic hyperplasia (BPH) pharmacotherapies, the alpha1-adrenergic blocker tamsulosin, is frequently discontinued, especially by younger patients due to ejaculatory disorders, often without feedback to the attending physician. Using a newly developed ex vivo system simulating sympathetic effects on the most relevant structures for the emission phase of ejaculation, that is seminal vesicles, prostate and the most distal part of the cauda epididymidis, we elucidated that tamsulosin fundamentally disturbed the obligatory noradrenaline-induced contractions in each of these structures which differed to an alternative pharmacotherapy, the PDE5 inhibitor tadalafil. Abstract: Structures responsible for the emission phase of ejaculation are the seminal vesicles, the most distal part of the cauda epididymidis and the newly characterized prostate excretory ducts. The emission phase is mainly regulated by the sympathetic nervous system through alpha1-adrenergic receptor activation by noradrenaline at the targeted organs. BPH treatment with alpha1A -adrenergic antagonists such as tamsulosin is known to result in ejaculation dysfunction, often leading to discontinuation of therapy. Mechanisms of this disturbance remain unclear. We established a rodent model system to predict drug responses in tissues involved in the emission phase of ejaculation. Imitating the therapeutic situation, prostate ducts, seminal vesicles and the distal cauda epididymal duct were pre-incubated with the smooth muscle cell-relaxing BPH drugs tadalafil, a novel BPH treatment option, and tamsulosin in an ex vivo time-lapse imaging approach. Afterwards, noradrenergic responses in the relevant structures were investigated to simulate sympathetic activation. Noradrenaline-induced strong contractions ultimately lead to secretion in structures without pre-treatment. Contractions were abolished by tamsulosin in prostate ducts and seminal vesicles and significantly decreased in the epididymal duct. Such effects were not observed with tadalafil pre-treatment. Data visualized a serious dysfunction of each organ involved in emission by affecting alpha1-adrenoceptors localized at the relevant structures but not by targeting smooth muscle cell-localized PDE5 by tadalafil. Our model system reveals the mechanism of tamsulosin resulting in adverse effects during ejaculation in patients treated for BPH. These adverse effects on contractility do not apply to tadalafil treatment. This new knowledge translates directly to clinical medicine.